Asuhan Keperawatan Pasien CA Mamae Post Kemoterapi Dengan Pemberian Intervensi Oral Hygiene Dengan NACL 0.9% Untuk Mengurangi Derajat Mukositis Di Ruang Cempaka RSU Kabupaten Tangerang - Lidia Rosaria; Meynur Rohmah; Dwi Wahyuni (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: Breast cancer is a disease condition in which abnormal cell proliferation occurs in the breast tissue which occurs quickly and uncontrollably, so this Final Scientific Work aims to identify nursing care for post-chemotherapy ca mammae patients by providing oral hygiene interventions with NaCl 0.9% which is useful for reducing the degree of mucositis. The method used in this case study was to provide nursing care for 3 days. The results obtained show that there are changes in pain, appetite and fatigue felt by patients as an effect of oral hygiene intervention with 0.9% NaCl which can help reduce post-chemotherapy complaints.